1998
DOI: 10.3733/ca.v052n04p14
|View full text |Cite
|
Sign up to set email alerts
|

Wind barriers offer short-term solution to fugitive dust

Abstract: Dust storms, like this one pictured along a county road in the Antelope Valley, have led to serious traffic accidents and violations of air quality standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Previous reviews indicate that (1) wind erosion reduces soil productivity because of the loss of plant nutrients, degradation of soil structure, loss of storage capacity for water for plants, and reduced uniformity of soil conditions within a field; (2) dust abrades and buries plants and blocks sunlight; and (3) aeolian deposition reduces reservoir storage capacity, clogs streams and drainage channels, deteriorates aquatic habitats, muddies recreational waters, damages water distribution systems and pollutes water systems with agricultural chemicals (Davis and Condra, 1989;Ervin and Lee, 1994;Grantz et al, 1998;Larney et al, 1998).…”
Section: Impacts Caused By Wind Erosion and Dustmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous reviews indicate that (1) wind erosion reduces soil productivity because of the loss of plant nutrients, degradation of soil structure, loss of storage capacity for water for plants, and reduced uniformity of soil conditions within a field; (2) dust abrades and buries plants and blocks sunlight; and (3) aeolian deposition reduces reservoir storage capacity, clogs streams and drainage channels, deteriorates aquatic habitats, muddies recreational waters, damages water distribution systems and pollutes water systems with agricultural chemicals (Davis and Condra, 1989;Ervin and Lee, 1994;Grantz et al, 1998;Larney et al, 1998).…”
Section: Impacts Caused By Wind Erosion and Dustmentioning
confidence: 98%
“…Methods of tilling to reduce entrainment of fine particles are evaluated by Grantz et al (1998), who found that furrows reduced aeolian dust 93% near the surface and from 24% to 33% above 1-m height, while increasing the threshold friction velocity for dust emission from about 45 to 65 cm s À 1 . High ridges may erode at their crests, and weathering of tracks and filling with deposition from subsequent events (Fig.…”
Section: Tillagementioning
confidence: 99%
See 2 more Smart Citations
“…Bringing subsoil to the surface can reduce erosion [Bunn, 1997]. Grantz et al [1998] found that the threshold wind friction velocity for dust emission increases from 45 cm/s to 65 cm/s (approximately 40%) due to tillage. Uri [1999] estimated that conservation tillage was used on nearly 36% of planted land in the U.S. in 1996.…”
mentioning
confidence: 99%